Cervical Spinal Cord Atrophy can be Accurately Quantified Using Head Images. Issue 1 (January 2022) - Taheri, Kamyar; Vavasour, Irene M; Abel, Shawna; Lee, Lisa Eunyoung; Johnson, Poljanka; Ristow, Stephen; Tam, Roger; Laule, Cornelia; Ackermans, Nathalie Chantal; Schabas, Alice; Cross, Helen; Chan, Jillian Katrina; et al.
Background: Spinal cord atrophy provides a clinically relevant metric for monitoring MS. However, the spinal cord is imaged far less frequently than brain due to artefacts and acquisition time, whereas MRI of the brain is routinely performed. Objective: To validate spinal cord cross-sectional area measurements from routine 3DT1 whole-brain MRI versus those from dedicated cord MRI in healthy controls and people with MS. Methods: We calculated cross-sectional area at C1 and C2/3 using T2*-weighted spinal cord images and 3DT1 brain images, for 28 healthy controls and 73 people with MS. Correlations for both groups were assessed between: (1) C1 and C2/3 using cord images; (2) C1 from brain and C1 from cord; and (3) C1 from brain and C2/3 from cord. Results and Conclusion: C1 and C2/3 from cord were strongly correlated in controls ( r = 0.94, p <0.0001) and MS ( r = 0.85, p <0.0001). There was strong agreement between C1 from brain and C2/3 from cord in controls ( r = 0.84, p <0.0001) and MS ( r = 0.81, p <0.0001). This supports the use of C1 cross-sectional area calculated from brain imaging as a surrogate for the traditional C2/3 cross-sectional area measure for spinal cord atrophy.